INTEGRATING COMPOST, CHEMICAL FERTILIZERS, AND PLANT GROWTH-PROMOTING RHIZOBACTERIA FOR IMPROVING PRODUCTIVITY OF PEA (Pisum sativum L.) - Muhammad Jamil; Sajid Masood; Muhammad Akram Qazi; Sarvet Jehan; Mehwish Liaquat; Atta Rasool; Muhammad Aon; Muhammad Umar Hayat Khan; Muhammad Khalid Rsheed (Journal of Animal and Plant Sciences, 2026)
Although chemical fertilizers provide essential nutrients, prolonged use of inorganic fertilizers not only deteriorates soil health but also damages crop yield. However, application of organic amendments like compost and plant growth-promoting rhizobacteria (PGPR) along with chemical fertilizers is considered as a sustainable approach for improving nutrient availability in soil-plant systems. A pot experiment was carried out according to completely randomized design (CRD) to assess their impact on pea (Pisum sativum L.) growth and yield. Following treatments: control, 100% NPK, 100% compost, 50% NPK + 50% compost both with and without PGPR (Bacillus subtilus RP-01) inoculation were established with four replications of each. The results revealed that plant growth and yield were highest in treatment T4 when PGPR-inoculated plants were subjected to 50% NPK + 50% compost. Organic amendment like 100% compost in conjunction with PGPR inoculation resulted in the maximum root nodulation (54.50 root nodules pot-1) and bacterial population (8x105 CFU g-1 fresh soil). By contrast, 100% compost and PGPR did not result in the maximum nutrient availability in soil-plant system as compared to inoculated 50% compost + 50% NPK. In conclusion, integration of 50% compost, 50% NPK and PGPR inoculation enhanced pea yield by 22.56% when compared with 100% NPK alone. Moreover, integrated approach like PGPR + 50% compost + 50% NPK enhanced pea yield by reducing NPK inputs up to 50%.
Keywords: Chemical fertilizers; Nodulation; Nutrient uptake; PGPR inoculation; Pea yield; Sustainable agriculture